Strategy for Developing Small and Medium Enterprises in Tahu Desa Laut Dendang, Deli Sedang Regency, Based on Maslahah - Dhea Rahma Novita; , Tri Inda Fadhila Rahma; , Nurul Jannah (Amkop Management Accounting Review (AMAR), 2025)
Micro, Small, and Medium Enterprises (MSMEs) development strategies have a very important role in supporting economic growth and improving community welfare, especially in rural areas. This study aims to analyze the development strategy of tofu MSMEs in Laut Dendang Village, Deli Serdang Regency, with a maslahah-based approach that focuses on social and economic benefits. The research method used is descriptive qualitative, with data collection through interviews, observations, questionnaires, and documentation. The analysis technique used is SWOT analysis, which identifies internal factors in the form of strengths (Strength) and weaknesses (Weakness), as well as external factors in the form of opportunities (Opportunity) and threats (Threat) to the development of tofu microbusinesses. The results showed an IFAS score value of 3.5626 and EFAS of 3.015, which placed tofu MSMEs in Laut Dendang Village in quadrant II, with an ST (Strength-Threat) strategy that can utilize internal strengths to overcome external threats. This strategy can be verified by utilizing strengths to deal with emerging threats. Tofu MSMEs in Laut Dendang Village have implemented the concept of maslahah in their business operations, which focuses on improving the social and economic welfare of the community. To develop the business further, strategies are needed that are in accordance with the principles of maslahah that have been applied, in order to strengthen business sustainability and increase positive impacts on the surrounding community.